Theoretical investigation of the non-degenerate four-wave mixing response for cyanine systems within the VB-CT model: Relation time”™s effects - Paz, J. L.; Squitieri, E. (Ciencia)
In this paper we present the calculations of the non-degenerate four wave-mixing (nd-FWM) signal for cyanine molecules in the context of the valence bond-charge transfer (VB-CT) model. In particular, we study the effect of alter the relation between the longitudinal (T1) and transversal (T2) relaxation times on this signal. As result of our calculations, only four peaks are observed in the nd-FWM spectrum in the frequency space, in contrast to twelve peaks observed for common push-pull chromophores. Moreover, significant changes in intensity and shape of the peaks of the nd-FWM spectrum with relation to the variation in the ratio between T1 and T2 were observed.